Bilateral Pelvic Kidneys in a Haemophiliac - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Renal migration anomalies are rare and often under-reported. Kidneys that fail to ascend to their normal location in the renal fossa are usually termed 'ectopic' kidneys, which can be unilateral or bilateral. Those that fail to ascend above the pelvic brim are commonly termed pelvic kidneys. We present a case of a 41-year-old male haemophiliac on routine investigation with a previous history of anaemia and bone pains, currently asymptomatic. He was found to have malrotated pelvic kidneys with vascular anomalies. Even though most patients with pelvic kidneys are asymptomatic, they are usually discovered in childhood or as young adults. This case is important because, in addition to the late discovery of the bilateral pelvic kidneys, there is coexistence of a bleeding disorder which may pose a challenge in patients' management. This is to also make the patient aware of his condition and avoid taken unnecessary risk which might make his condition worse.